2020
DOI: 10.3389/fimmu.2020.01779
|View full text |Cite
|
Sign up to set email alerts
|

A Rosetta Stone for Breast Cancer: Prognostic Value and Dynamic Regulation of Neutrophil in Tumor Microenvironment

Abstract: Increasing evidence has revealed that the initiation and progression of breast cancer are greatly affected by the immune environment. Neutrophils are the most abundant leucocytes in circulation and act as the spearhead in inflammation, including in breast cancer. Circulating neutrophils are closely related to the prognosis of breast cancer patients, and tumor-infiltrating neutrophils have varied functions at different stages of breast cancer, such as antitumor or tumor-promoting neutrophils, which are termed N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 167 publications
(183 reference statements)
0
36
0
Order By: Relevance
“…While a different function of TILs across the different breast cancer subtypes has been demonstrated, as described above, very little is known about the role and activation of neutrophils. Neutrophils are emerging as major players in defining the fate of cancer development, promoting tumor growth and progression towards a metastatic disease or favoring killing of tumor cells and cancer regression [ 60 ]. The first scenario has been highlighted by a meta-analysis of the association between tumor-associated neutrophils (TANs) and prognosis in different cancer types [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a different function of TILs across the different breast cancer subtypes has been demonstrated, as described above, very little is known about the role and activation of neutrophils. Neutrophils are emerging as major players in defining the fate of cancer development, promoting tumor growth and progression towards a metastatic disease or favoring killing of tumor cells and cancer regression [ 60 ]. The first scenario has been highlighted by a meta-analysis of the association between tumor-associated neutrophils (TANs) and prognosis in different cancer types [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The former is mainly determined by exposure of neutrophils to type-I interferon [ 65 ]; the latter is prompted by transforming growth factor (TGF)-β [ 64 , 66 , 67 ] and granulocyte colony-stimulating factor (G-CSF) [ 68 ]. N1 neutrophils exert an anti-tumor effect through the production of hypochlorous acid (HOCl), reactive oxygen species (ROS), tumor necrosis factor (TNF)-α, and nitric oxide (NO) and promote an immunogenic microenvironment by inhibiting interleukin (IL)-17 production and exhibiting increased antibody-dependent cell cytotoxicity (ADCC) [ 60 ]. To the contrary, N2 neutrophils support tumor growth through the production of vascular endothelial growth factor (VEGF), IL-1β, IL-6, and IL-17, promote an immune-suppressive microenvironment by recruiting Treg, and favor the metastatic process by inducing neutrophil extracellular trap (NET) formation [ 60 ], a type of neutrophil death leading to the release of DNA–histone complexes and proteins to form net-like structures.…”
Section: Discussionmentioning
confidence: 99%
“…S100A-8, S100A-9, CXCL-1, and CXCL-2), tissue-remodeling enzymes (MMP-3 and MMP-9) and COX-2 during mammary involution [ 31 ]. Protumoral neutrophils exacerbate the formation of tumor-promoting microenvironment, which further encourages BC progression [ 31 , 32 ].…”
Section: The Effects Of Estrogen On the Immune Systemmentioning
confidence: 99%
“…Moreover, neutrophils are involved in the immune response, as an important part of the tumor microenvironment, which plays a central role in cHL pathogenesis [11][12][13]. Neutrophil counts and neutrophil/lymphocyte ratio (NLR) have been proposed as prognostic factors in several solid and hematological tumors, including adults with cHL [14][15][16][17][18][19][20]. A recent study demonstrated that NLR could predict clinical outcomes in PET-negative adult patients with cHL [21].…”
Section: Discussionmentioning
confidence: 99%